Impulse Noise Considerations Related to Data Transmission over High-voltage Lines - Krejci, J.; Zeman, T.; Hrad, J. (Elektronika ir Elektrotechnika, 2014)
This paper describes methods for theoretical modeling of inter-arrival time of impulse noise and presents a new model based on the application of general mathematical distributions, together with its implementation in MATLAB. It also discusses the suitability of this model for development and testing of digital communication systems intended for deployment on high-voltage power distribution lines. DOI: http://dx.doi.org/10.5755/j01.eee.20.8.8444